Synthesis and analysis of ZnO and CdSe nanoparticles - Ashtaputre, S. S.; Deshpande, Aparna; Marathe, Sayali; Wankhede, M. E.; Chimanpure, J.; Pasricha, R.; Urban, J.; Haram, Santosh K.; Gosavi, S. W.; Kulkarni, S. K. (Pramana-Journal of Physics, 2005)
Zinc oxide and cadmium selenide particles in the nanometer size regime have been synthesized using chemical routes. The particles were capped using thioglycerol in case of ZnO and 2-mercaptoethanol in case of CdSe to achieve the stability and avoid the coalescence. Zinc oxide nanoparticles were doped with europium to study their optical properties. A variety of techniques like UV-Vis absorption spectroscopy, X-ray diffraction (XRD), photoluminescence (PL), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR) and transmission electron microscopy (TEM) were used to carry out structural and spectroscopic characterizations of the nanoparticles.
Keywords: chemical capping; Doping; Nanoparticles; photoluminescence

Citrate-capped quantum dots of CdSe for the selective photometric detection of silver ions in aqueous solutions - Ingole, Pravin P.; Rajiv M. Abhyankar; Bhagavatula L. V. Prasad; Haram, Santosh K. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
A simple strategy for the synthesis of water soluble, luminescent, citrate-capped CdSe quantum dots (Q-CdSe) and their applications to selective detection of silver ions are described. The steady state photoluminescence (PL) spectra show single, narrow emission band at ca. 554 nm without any contribution from the trap states. The effect of various ions including physiologically important metal ions (viz. K(+), Ca(2+), Fe(3+), Zn(2+), Mg(2+), Mn(2+), Cu(2+), Ag(+), Pb(2+) and Cd(2+)), on the PL intensity of citrate-capped Q-CdSe has been studied. Among these, selective luminescence quenching with Ag(+) ion was found to be predominant. Under the optimum conditions, the response was linear between 1.7 and 18 mu M. The quenching constant K(SV) was found to be ca. 3.4 x 10(5) M(-1). The mechanism of photoluminescence quenching of Q-CdSe by metal ions (Ag(+)) is also discussed. Based on these studies, the potential use of Q-CdSe as a luminescent probe for the selective detection of silver ion has been proposed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ag(+) ions; Luminescence quenching; Luminescent probe; Q-CdSe; Tri-sodium citrate

Fabrication, characterization and electrochemical performance of single strand carbon fiber prepared by catalytic chemical vapor decomposition method - Joshi, Vrushali S.; Gokhale, Suresh P.; Patil, Kashinath R.; Haram, Santosh K. (Electrochimica Acta, 2010)
Preparation, fabrication and voltammetric characterizations of a single strand of carbon fiber (SSCF) electrode and their potential applications for biosensor are presented. SSCFs of diameter ca. 10 +/- 2 mu m and few millimeters in length are prepared by catalytic chemical vapor decomposition (CCVD) method. Voltammetry with potassium ferricyanide. alpha-methylferrocene methanol and hexaammineruthenium(III) chloride on SSCF electrode are used as bench marks to validate the electrode properties. Quasi-steady state voltammograms obtained were fitted into a cylindrical diffusion model From which, the standard rate constant (k(0)) and electron transfer coefficient (alpha) are obtained. The use of SSCF electrode is demonstrated for the voltammetric detection of the micromolar quantity of dopamine in the presence of large excess (ca. 200 times) of ascorbic acid, without any fouling of electrode surface. The kinetics of electron transfer are investigated. (C) 2009 Elsevier Ltd All rights reserved.
Keywords: alpha-Methylferrocene methanol; Ascorbic acid; Catalytic chemical vapor decomposition (CCVD); Cylindrical diffusion; dopamine; Hexaammineruthenium(III) chloride; Single strand carbon fiber (SSCF) electrode

Synthesis and molecular structure of a zinc complex of the vitamin K-3 analogue phthiocol - Kathawate, Laxmi; Sproules, Stephen; Pawar, Omkar; Markad, Ganesh; Haram, Santosh K.; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2013)
The complex [Zn(phthiocol)(2)(H2O)(2)]; 1, where phthiocol is 2-hydroxy-3-methyl-1,4-naphthoquinone, has been synthesized and characterized by elemental analysis, FT-IR, H-1 NMR, UV-vis spectroscopy, thermogravimetric (TG) analysis, electrochemical and single crystal X-ray diffraction studies. The v(C=O) stretch shifts to lower frequencies upon complexation of phthiocol to Zn2+. H-1 NMR spectra show an upfield shift of the benzenoid ring protons in 1. There is a bathochromic shift of the LMCT band in the UV-vis spectra of 1. Single crystal X-ray structure of 1 show distorted octahedral geometry around Zn2+. Two phthiocol ligands are in plane with the metal, while water molecules are trans to this plane. Coordination of deprotonated phthiocol ligands is `trans, trans' to Zn2+. Intra as well as intermolecular interactions are observed in 1. Molecules of 1 show three dimensional network through C-H center dot center dot center dot O and O-H center dot center dot center dot O interactions. Additional anodic peaks are observed in cyclic voltammogram of phthiocol ligand due to oxidation of reduced species formed during reduction. One-electron reduction of 1 is shown to be reversible and DFT studies define this redox event as ligand-centered. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: hydrogen bonding; Naphthoquinone; Phthiocol; Trans coordination; Vitamin K-3; Zinc complex

Molecular structures and biological evaluation of 2-chloro-3-(n-alkylamino)-1,4-napthoquinone derivatives as potent antifungal agents - Pawar, Omkar; Patekar, Ashwini; Khan, Ayesha A.; Kathawate, Laxmi; Haram, Santosh K.; Markad, Ganesh; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2014)
Derivatives of 2-chloro-3-(n-alkylamino)-1,4-naphthoquinone (1-alkyl: methyl; L-1, ethyl; L-2, propyl; L-3 and butyl; L-4) have been synthesized and characterized by elemental analysis, FT-IR, H-1 NMR, UV-visible spectroscopy, LC-MS and single crystal X-ray diffraction studies. Antifungal activity of L-1 to L-4 has been evaluated against Candida tropicalis, Candida albicans and Cladosporium herbarum. The intramolecular hydrogen bonding affects the N-H vibrational frequency in L-2 (3273 cm(-1)). The single crystal X-ray structure reveal that L-1 and L-3 crystallizes in triclinic P-1, whereas L-2 crystallizes in orthorhombic Pca2(1), space group. An extensive intra and intermolecular hydrogen bonding interactions were observed in L-1 to L-3 which leads to molecular association. Intramolecular N-H center dot center dot center dot O hydrogen bonding were observed in L-1 to L-3. Moreover pi-pi stacking interactions were observed between the quinonoid rings of L-1 and L-3, however no such interactions were observed in L-2. An electrochemical study showed molecular association of L-1 to L-4 in DMSO solution. Compounds L-1 to L-4 were found to be potent antifungal agents against all the three strains, especially against C. tropicalis. Amongst these promising antifungal candidates, L-1 showed better activity compared to the clinically administered antifungal drug Amphotericin B and Nitrofurantoin with MIC = 1.25 mu g ml(-1) and MIC = 0.025 mu g ml(-1) respectively against C. albicans. Structure and activity relationship (SAR) study suggest a LogP value of similar to 2.0 and the cyclic voltammetry studies reveals additional chemical processes for L-1, which exhibits maximum activity against all fungal strains. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone; Antifungal activity; LogP; Naphthosemiquinone; pi-pi stacking

Role of iron oxide impurities in electrocatalysis by multiwall carbon nanotubes: An investigation using a novel magnetically modified ITO electrodes - Samant, Kanchan M.; Joshi, Vrushali S.; Patil, Kashinath R.; Haram, Santosh K. (Bulletin of Materials Science, 2014)
The role of iron oxide impurities in the electrocatalytic properties of multiwall carbon nanotubes (MWCNTs) prepared by catalytic chemical vapour decomposition method (CCVD) is studied in detail. A novel magnetically modified electrodes have been developed by which MWCNTs were immobilized on indium-tin oxide (ITO) electrodes, without any chemical binders. The electro-catalytic oxidation of dopamine, and reduction of hydrogen peroxide have been studied by cyclic voltammetry on magnetically modified electrodes with (i) MWCNTs with occluded iron oxide impurities (Fe-MWCNTs), (ii) MWCNTs grown on iron oxide nanoparticle particulate films (Io-MWCNTs) and (iii) pristine iron oxide nanoparticle particulate film (Io-NPs). A shift towards less positive potentials for the oxidation of dopamine was observed which is in the order of Fe-MWCNTs < Io-MWCNTs < Io-NPs. Similarly, trend towards less negative potentials for the reduction of hydrogen peroxide was observed. Thus, the electrocatalytic activities displayed by MWCNTs have been attributed to the iron oxide impurities associated with it. The systematic variation was related to the nature of interaction of iron oxide nanoparticles with MWCNT surface.
Keywords: dopamine; Hydrogen peroxide; iron oxide nanoparticles; magnetically-modified electrode; Multiwall carbon nanotubes (MWCNTs)

Reduction of graphene oxide by 100 MeV Au ion irradiation and its application as H2O2 sensor - Hareesh, K.; Joshi, R. P.; Shateesh, B.; Asokan, K.; Kanjilal, D.; Late, Dattatray J.; Dahiwale, S. S.; Bhoraskar, Vasant N.; Haram, Santosh K.; Dhole, Sanjay D. (Journal of Physics D-Applied Physics, 2015)
Graphene oxide (GO) synthesized from a modified Hummer's method was reduced (referred, rGO) by using 100 MeV Au ion species and its response to the sense H2O2 was investigated. The changes in the atomic composition and structural properties of rGO after irradiation were studied using x-ray diffraction, Fourier transform infrared spectroscopy and x-ray photoelectron spectroscopy. These results suggested that the removal of the oxygen-containing functional groups and the improvement of the electrochemical performance of reduced graphene oxide (rGO) after ion irradiation. Raman spectroscopic results revealed the increase in the disorder parameter (I-D/I-G) after Au ion irradiation and also the formation of a large number of small sp(2) domains due to the electronic energy loss of ion beam. The resultant rGO was investigated for H2O2 sensing using electrochemical techniques and it showed a good response.
Keywords: electronic energy loss; GO; ion beam irradiation; reduction

In situ electrochemical transformation of Ni3S2 and Ni3S2-Ni from sheets to nanodisks: towards efficient electrocatalysis for hydrogen evolution reaction (HER) - Busupalli, Balanagulu; Battu, Shateesh; Haram, Santosh K.; Bhagavatula L. V. Prasad (Chemistryselect, 2016)
Transition metal sulphides have been viewed as alternatives to platinum based electrocatalysts for HER. Herein, we report the preparation of Ni3S2 in conjunction with Ni in a novel nanosheet morphology and verified its performance for HER. During cyclic polarization, exotic morphological transformation of Ni-3 S-2-Ni from nanosheets to nanodisks has been noted. This change is accompanied with initial increase in over-potential that passed through maxima (similar to 100mV above the starting potential) and decreased to similar to 50mV below the starting value. Enhanced electrocatalytic activity due to the morphological changes from sheets to nanodisks has been attributed to the formation of more number of exposed edge-planes known to promote HER. Kinetic analysis based on Tafel slope displayed by this composite is comparable to that of Pt based catalysts.

Methanol oxidation reaction on Pt based electrocatalysts modified ultramicroelectrode (UME): Novel electrochemical method for monitoring rate of CO adsorption - Joshi, Vrushali S.; Poudyal, Durgasha C.; Satpati, Ashis K.; Patil, Kashinath R.; Haram, Santosh K. (Electrochimica Acta, 2018)
Novel fast scan cyclic voltammetry (FSCV) based method has been developed to study methanol oxidation reaction on Pt nanoparticles (PtNPs) based catalysts. To support the cyclic voltammetry measurements at higher scan rates, micron-sized electrode geometries viz. PtNPs loaded on the single strand of carbon fiber (SSCF) and PtNPs decorated multiwalled carbon nanotubes (MWCNTs), loaded on commercial ultramicroelectrode (UME) have been employed. Deconvolution of the voltammograms obtained during methanol oxidation revealed three major anodic peaks. These peaks have been plausibly attributed to the electron transfer processes viz. methanol oxidation into CO/other intermediates, oxidation of these intermediates into CO2 and adsorption of un-oxidized CO on the catalyst surface. The peaks due to CO adsorption have been elucidated as a function of scan rates. The area under the peak as a function of time has been correlated to the rate of CO adsorption on these catalysts. The average rate of CO adsorption in methanol oxidation at Pt-SSCF and Pt-MWCNTs/UME are estimated to be 1.08 x 10(-8) mol cm(-2) s(-1) and 13.5 x 10(-8) mol cm(-2) s(-1) respectively. This novel method is proposed to generalize to any electrocatalysts of interest. (C) 2018 Published by Elsevier Ltd.